Peningkatan Kreativitas Mahasiswa melalui Praktikum Biokimia berbasis Bahan Alam - Firdiawan Ekaputra (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study examines the effectiveness of implementing natural material-based biochemistry practicums in enhancing university students’ creativity. The research is grounded in the recognition that creative thinking skills among students have not been optimally facilitated within conventional laboratory instruction. Employing a one-group pretest–posttest research design, this study measured changes in students’ creativity before and after their participation in biochemistry practicums utilizing natural materials. The participants consisted of 23 students enrolled in the Biochemistry Practicum course within the Chemistry Education Study Program. Data were collected using a Likert-scale questionnaire that assessed four dimensions of creativity: idea fluency, flexibility, originality, and elaboration. Statistical analysis revealed a significant increase in students’ creativity following the intervention, as indicated by a significance value of 0.000. These findings demonstrate that natural material-based biochemistry practicums are effective in fostering students’ creative capacities. The study concludes that integrating natural materials into biochemistry laboratory activities constitutes a pedagogically meaningful strategy to promote creativity, encourage exploratory learning, and strengthen the practical application of biochemical concepts in higher education contexts.